Impact of Systemic Inflammatory Response Syndrome on Clinical, Echocardiographic, and Computed Tomographic Outcomes Among Patients Undergoing Transcatheter Aortic Valve Implantation - Ahmed, Tarek A. N.; Ki, You-Jeong; Choi, You-Jung; El-Naggar, Heba M.; Kang, Jeehoon; Han, Jung-Kyu; Yang, Han-Mo; Park, Kyung Woo; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Hyo-Soo (Frontiers in Cardiovascular Medicine, 2022)
Background Systemic inflammatory response syndrome (SIRS) is a systemic insult that has been described with many interventional cardiac procedures. The outcomes of patients undergoing transcatheter aortic valve implantation (TAVI) are thought to be influenced by this syndrome not only on short-term, but also on long-term. Objective We assessed the association of SIRS to different clinical, echocardiographic, and computed tomographic (CT) outcomes after TAVI. Methods Two hundred and twenty-four consecutive patients undergoing TAVI were enrolled in this study. They were assessed for the occurrence of SIRS within the first 48 h after TAVI. Patients were followed-up for short- and long-term clinical outcomes. Serial echocardiographic follow-ups were conducted at 1-week, 6-months, and 1-year. CT follow-up at 1 year was recorded. Results Eighty patients (36%) developed SIRS. Among different parameters, only pre-TAVI total leucocytic count (TLC), pre-TAVI heart rate, and post-TAVI systolic blood pressure independently predicted the occurrence of SIRS. The incidence of HALT was not significantly different between both groups, albeit higher among SIRS patients (p = 0.1) at 1-year CT follow-up. Both groups had similar patterns of LV recovery on serial echocardiography. Long-term follow-up showed that all-cause death, cardiac death, and re-admission for heart failure (HF) or acute coronary syndrome (ACS) were significantly more frequent among SIRS patients. Early safety and clinical efficacy outcomes were more frequently encountered in the SIRS group, while device-related events and time-related valve safety were comparable. Conclusion Although SIRS implies an early acute inflammatory status post-TAVI, yet its clinical sequelae seem to extend to long-term clinical outcomes.